KEANEKARAGAMAN HYMENOPTERA PARASITOID PADA STURUKTUR LANSKAP PERTANIAN BERBEDA DI DAERAH ALIRAN SUNGAI (DAS) CIANJUR, JAWA BARAT - Yaherwandi, S. Manuwoto, D. Buchori2, P. Hidayat, dan L.B. Prasetyo. (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2007)
Diversity of Hymenoptera Parasitoid in Different Agricultural Landscape at Cianjur Watershed, West Java. Understanding how the landscape structure affect the interaction between crops, pests and their natural enemies is a complex problem that can significantly impact on the success or failur of insect biological control. Hymenoptera parasitoid are particularly important natural enemies because of their great diversity and effectiveness as agents of biological control. The objective of this research is to study the diversity of Hymenoptera parasitoid in rice field at Cianjur Watershed. Insects were sampled using three trapping techniques (farmcop, insect net and yellow pan trap). Species accumulative curves, Jackknife-1 estimator, indices of diversity, indices of community similarities and cluster analysis were applied to analyze the data. Results indicated that there were 2750 speciment consist of 26 family and 325 species of Hymenoptera parasitoid in rice fields at Cianjur Watershed. Diversity of Hymenoptera parasitoid were found to be influenced by the landscape structure and seasone of ricefield. Species richness and diversity were higher in Nyalindung landscape than Gasol and Selajambe landscape.